“Let my people live in Peace” (Hekima Review, 2014)
Security is a word that we hear almost on a daily basis indicating how central it is in our lives. As put by the prophet Isaiah, the Lord always desires his people to be in peace, “My people will live in peaceful country, in secure dwellings and quiet resting places.” (Isaiah 32:18.) This wish is fulfilled through the efforts of all. “No man is built up by wickedness, but the root of the just will never be disturbed.” (Prov. 12:3). Human security: a Theological and Peace Perspective is a move to building up roots of justice and security in today’s society. The search for and promotion of human security is the responsibility of every human person. The struggle for human security is for everyone because everyone deserves it. It is not a matter of give and take but rather a give without counting the cost. Aware now more than ever human security means much more than the absence of conflict. Inspired by the day to day realities that are affecting individuals, groups of persons, societies, nations and races we reflect on the reality of human security.What in thisworld is promoting this important aspect of human beings and what is diminishing or affecting it negatively? United Nations Trust Fund for Human Security, “Human security is a dynamic and practical policy framework for addressing widespread and cross-cuttingthreats facing Governments and people.”